(untitled) (Medico Legal Update, 2020)
Renal dialysis patients face many challenges during the treatment period and are subjected to many psychological stresses, but depressive symptoms of dialysis patients are associated with higher mortality. This study aims to assess the level of depression in patients with chronic renal disease undergoing haemodialysis treatment; 60 patients with chronic renal failure receiving haemodialysis treatment were recruited from Al-Hussian hospital in one of the religious cities in Iraq. Depression was assessed using the Beck Depression Inventory.The results showed that most participants had severe and extreme levels of depression, and higher scores were representative of somatic depressive symptoms. There was no significant association between depression and patient demographic data. Depression should be assessed by nurses, and patients should be referred for treatment to decrease mortality and improve disease outcome.